Family Farm as an Organization Form of the Agricultural Industry in the Concept of Sourcing and Purchasing Management - Vladimir Egorov; Evgeniya Shavina; Andrey Inshakov (International Journal of Supply Chain Management, 2019)
Abstract- Scientific development of family farms problem, in addition to academic interest, is of great practical importance for the global economy as a whole (more than 90% of households in the agricultural sector in the world are family-run, family farms account for up to 80% of agricultural land farms produce about 80% of the world food) and the Russian agrarian sector in particular. In the current academic discourse and the world practice in agricultural sector, food supply of the population, a vertically integrated organization that has been hampering the optimization of the value of agricultural goods based on the choice of an adequate supply chain management strategy is increasingly criticized. The authors considered theoretical approaches to family farming as a special form of social-and-economic organization, which is the most reliable mechanism for mass recruitment of rural population into the economy and optimization of material and information flows, cooperative ties of value creating participants in order to satisfy consumers in comparison with large agricultural holdings. The US experience indicates the possibility of harmonious combination of developed industry and commodity family farms in economic complexes. Due to their small scale, family farms, being more adaptive to market conditions and, therefore, more sustainable, combine in themselves strategies of commodity production and personal consumption, and also reproduce traditional moral norms. In this regard, the organization of agriculture in the form of family farms is the most adequate form of food supply for the population. Family commodity farms, among other things, are the best form in terms of supply chain management, as they shorten the distance between production and consumption as much as possible.